1975
DOI: 10.1104/pp.55.4.738
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Kinetin and Calcium in Relation to Their Effect on Stimulation of Ethylene Production

Abstract: Application of kinetin and Ca2+ caused a striking synergistic increase in ethylene production by mung bean (Phaseolus aureus Roxb) hypocotyl segments. The effect of kinetin on Ca2+ uptake and of Ca'+ on the uptake and metabolism of kinetin in relation to their effect on ethylene production was studied. Tracer experiments showed that kinetin greatly increased the uptake of 4"Ca2' after 6 hours of incubation. Reciprocallv, Ca2+ stimulated the uptake of kinetin-8-14C and remarkably enhanced the metabolism of kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…During the course of the study of the synergistic stimulation of ethylene by kinetin and Ca2 , we found that kinetin greatly enhanced the uptake of Ca2+ into the tissue, with a lag period of about 5 hr, which corresponds to the time required for induction of ethylene production (15). Our results are compatible with the view that kinetin plays a role by releasing and transporting Ca2+ from cell wall to an intracellular site where Ca2+ is required for ethylene biosynthesis.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…During the course of the study of the synergistic stimulation of ethylene by kinetin and Ca2 , we found that kinetin greatly enhanced the uptake of Ca2+ into the tissue, with a lag period of about 5 hr, which corresponds to the time required for induction of ethylene production (15). Our results are compatible with the view that kinetin plays a role by releasing and transporting Ca2+ from cell wall to an intracellular site where Ca2+ is required for ethylene biosynthesis.…”
Section: Methodssupporting
confidence: 80%
“…We have found that kinetin greatly enhances the uptake of Ca2+ with a lag period of 6 hr which corresponds to the time required for induction of ethylene production. We suggested that the synergism between kinetin and Ca2+ on ethylene production is due to the enhanced intake of Ca2+ by kinetin into a specific site for ethylene production (15 Figure 1, the pattern of ethylene production in the Sr2+ plus kinetin system was identical to the Ca2+ plus kinetin system, indicating that Sr2+ can substitute for Ca2+ in the present system. The magnitude of ethylene production in response to Sr2+ was dependent on Sr2+ concentration (Fig.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…Yet other studies identified a Ca 21 / cytokinin/ethylene connection, although there was disagreement between published reports on the nature of the interaction. Lau and Yang (1975), in studies on mung bean hypocotyl segments, reported that kinetin greatly stimulated uptake of 45 Ca 21 , and Ca 21 stimulated the uptake and metabolism of kinetin 14 C. Of particular note, both Ca 21 and kinetin caused a striking increase in ethylene (Lau and Yang, 1975). By contrast, Poovaiah and Leopold (1973a), in studies of leaf abscission in bean petiole explants, found that Ca 21 inhibited ethylene production.…”
Section: Ca 21 and Plant Growth Regulatorsmentioning
confidence: 97%